ICT Update 75: ICT4Ag - making it happen - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2013)
ICT Update is a bimonthly printed and on-line magazine (http://ictupdate.cta.int) and an accompanying e-mail newsletter published by CTA. The 2013 ICT4Ag conference in Rwanda was unique in that it brought together the ICT and agricultural sectors and generated a clear list of action points for the community.